Starters. green book 1 - Flowerdew, Phyllis; Bellwood, Shirley (Oliver & Boyd Edinburgh, 1985)
Starters is a dystopian science fiction novel by Lissa Price, set in a future where a biological war has wiped out everyone except the young (Starters) and the elderly (Enders). The story follows Callie, a teenage girl who, in a desperate attempt to survive, rents her body to wealthy Enders who want to experience youth again through a body-bank program. But when Callie regains consciousness during one of the rentals, she uncovers a dark conspiracy that threatens her life and the lives of others. Filled with suspense, mystery, and high-stakes action, Starters is the first book in the Starters series, blending futuristic adventure with a compelling moral dilemma.